(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2019)
This article seeks to observe the Mapuche religious fact, starting from Rudolf Otto’s reflection on the numinous and the holy. For this, it uses its methodology of phenomenological analysis applied to the concepts of mysterium, tremendum and fascinans or the dimensions of fear, incorporated in the Mapuche culture. It is concluded that the analysis of these different moments of the saint-numinous experience in the religious life of the mapuche, allows to verify the dynamism existing in the religious idea of the mapuche, which in turn represents adequately the relationship between religious man and the Holy.